Giving Shape to a Meaningful and Fulfilling Career in Science: Some No‐Nonsense Advice - Kamini Singha (Perspectives of Earth and Space Scientists)
Abstract In this manuscript, I provide ideas that may help early‐career colleagues on their paths in science, especially in research and academia. I discuss the inevitability of failure at times, the importance of finding great collaborators and mentors and making time for the things that bring you joy in your life, and suggest a few practices that I hope make us more pleasant human beings. I share a few difficulties I've navigated and advice I've shared with my students, postdocs, and early‐career colleagues through the years. I hope such thoughts are useful, and help others find the joy in being a scientist.